PENGEMBANGAN MODUL BERBASIS ANDROID PADA MATERI STRUKTUR DAN FUNGSI TUMBUHAN - Fitriyah, Lailatul; Wahyuni, Eva Ari; Rosidi, Irsad; Qomaria, Nur; Tamam, Badrud (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
This study aims to determine the feasibility of the Android-Based Module for the science learning process, especially on the material Structure and Function of Plants and to determine the responses of students in MTs. Raudlatul Ulum Klampis Bangkalan Regency on the developed media. This type of research uses development research using the ADDIE model. The population of this study were students of class VIII junior high school and the sample in this study used class VIII B. Data was collected by conducting observations, questionnaires, and documentation. The results that can be seen from the three instruments are: 1) 84.375% percentage for the validity value of the media with very suitable criteria for use, 2) for the material used, the percentage value is 87.5% with very good criteria, 3) percentage for average – the average student response questionnaire was obtained by 89% with very good criteria.